2016
DOI: 10.5888/pcd13.160111
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for Increased Physical Activity in the Workplace: the Walking Meeting (WaM) Pilot Study, Miami, 2015

Abstract: IntroductionDespite the positive impact walking has on human health, few opportunities exist for workers with largely sedentary jobs to increase physical activity while at work. The objective of this pilot study was to examine the implementation, feasibility, and acceptability of using a Walking Meeting (WaM) protocol to increase the level of work-related physical activity among a group of sedentary white-collar workers.MethodsWhite-collar workers at a large university were invited to participate in a newly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The Community Guide recommends point-of-decision prompts to encourage individuals to use stairs [ 20 ], which is not always feasible for small businesses that may be located on a single level. Small businesses should consider supporting other strategies to incorporate PA into the day, such as walking meetings, when feasible [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Community Guide recommends point-of-decision prompts to encourage individuals to use stairs [ 20 ], which is not always feasible for small businesses that may be located on a single level. Small businesses should consider supporting other strategies to incorporate PA into the day, such as walking meetings, when feasible [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, “walking meetings” are proposed to increase physical activity and decrease workplace-sitting time by walking while holding meetings with colleagues. In a 3 week pilot study by Kling et al [ 67 ], the researchers found that implementing walking meetings resulted in an increased average walking time from an average of 107 min during the baseline week to 114 min at week 2 and to 117 min at week 3. According to the authors, the intervention was easy to implement, well accepted by the white-collar workers, and successful at increasing PA levels.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding walking meetings, a 3-week pilot-study with 17 participants yielded positive evaluations of a structured scheme with a single 30-min walking meeting per week [5]. However, a qualitative evaluation of a multicomponent intervention among 129 office workers found walk-talk meetings and lunchtime walking groups to be the least used strategies [16].…”
Section: Discussionmentioning
confidence: 99%
“…One element often included in such interventions is standing and walking meetings. However, only very little research has been done into this area, with studies being pilot studies or focusing on the perceptions of standing and walking meetings [4][5][6][7]. Additionally, a review of sitting time interventions at the workplace by Shrestha et al [3] concluded that there were no studies specifically investigating the effects of standing or walking meetings on sitting time.…”
Section: Introductionmentioning
confidence: 99%